Konsep Rencana Pengembangan Lansekap Subak Sebagai Kawasan Agrowisata Berkelanjutan - YUSIANA, LURY SEVITA; MAYADEWI, NI NYOMAN ARI (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017, 2017)
ABSTRACT Concept of Subak Landscape Development Plan As a Sustainable Agrotourism Area Subak is one of the world cultural heritage. However, the rapid development of tourism in Bali threatens the existence of the subak. The high price of land becomes unequal to farmers' income from the agricultural sector. Agricultural sector began to be abandoned and the existence of subak began to disappear. To reduce these threats, it is necessary to develop agricultural areas by focusing on the productivity of the performances that produce quality commodities and the development of agricultural landscape potential as a tourist destination. This study aims to plan the concept for the development of agricultural and subak areas as the motor of the agricultural sector to obtain economic opportunities through the tourism sector. The research method is done by analyzing agriculture sector through subak component (Windia, 2013) and analyzing the plan of arrangement of tourist landscape through tourism development component (Inskeep, 1991). The final product of this research is the concept of sustainable agro-tourism plan on the subak landscape. Keywords: subak, agrotourism, tourism landscape planning